Penelitian Pengolahan Air Sungai Yang Tercemar Oleh Bahan Organik - Yayu Sofia (Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2010)
In the water quality management, besides monitoring it is also need to treat polluted river water. The treatment of polluted river water can be done by physical method such as reaeration, precipitation and filtration. The research on treatment of polluted river water (River Cimuka) was conducted at Desa Sukabirus, Kecamatan Margaasih, Kabupaten Bandung. There are 3 systems to be studied in this research that is reaeration, precipitation dan filtration. The result shows that the most suitable system for river water teratment is the aeration system, that is to pass to blocking wall reaeration chanel.Data from this research show that the river water treatment system can increase thedissoleved oxygen up to 300% and decreasing the organic pollutant in the form of KMnO4 value 11%, 20% of BOD and 12% of COD. The other pollutan such as suspended solid also decrease up to 26%, 23% for turbidity up to 23% and total ammonia up to 33%.